Effect of once-daily fluticasone furoate/vilanterol versus vilanterol alone on bone mineral density in patients with COPD: a randomized, controlled trial. (October 2020) - Maltais, Francois; Schenkenberger, Isabelle; Wielders, Pascal L. M. L.; Ortiz de Saracho, Juan; Chinsky, Kenneth; Watkins, Michael; Millar, Valerie; Crim, Courtney
Background: The relationship between inhaled corticosteroids and bone mineral density (BMD) remains uncertain despite extensive research. Methods: This was an international, multicenter, randomized, double-blind, parallel-group, 3-year noninferiority study. Patients with chronic obstructive pulmonary disease (COPD) (⩾40 years of age; smoking history ⩾10 pack years) and at least one native hip evaluable for BMD were enrolled and randomized 1:1, stratified by sex, to treatment with vilanterol (VI) 25 µg or fluticasone furoate/vilanterol (FF/VI) 100 µg/25 µg. BMD measurements were taken via dual-energy X-ray absorptiometry every 6 months. The primary endpoint was assessment of the noninferiority of change from baseline in total hip BMD per year at the −1% noninferiority level. Change from baseline in BMD at the lumbar spine and BMD measurements by sex were secondary endpoints. Incidences of COPD exacerbations and bone fractures throughout the study were also recorded. Results: Of 283 randomized patients, 170 (60%) completed the study. Noninferiority was demonstrated for FF/VI versus VI with regards to change from baseline in total hip BMD per year, with changes of −0.27% and 0.18%, respectively, and a treatment difference of −0.46% per year [95% confidence interval (CI) −0.97 to 0.06]. The treatment difference for FF/VI versus VI regarding lumbar spine BMD was −0.51% per year (95% CI −1.11 to 0.10). COPD exacerbations and bone fracture rates were similar between treatment groups. Conclusion: FF/VI showed noninferiority to VI for change from baseline in total hip BMD per year, when assessed at the −1% noninferiority margin in a combined sample of men and women with COPD. The reviews of this paper are available via the supplemental material section.